Effects of educational program based on Precede-Proceed model in promoting low back pain behaviors (EPPLBP) in health care workers Shahid Beheshti University of medical sciences: randomized trial. Issue 10 (October 2020) - Pourhaji, Fatemeh; Delshad, Mohammad Hossein; Tavafian, Sedigheh Sadat; Niknami, Shamsodin; Pourhaji, Fahimeh
Abstract: The PRECEDE-PROCEED model is an adaptable planning model that could be served in public health issues. The purpose of this study is to investigate the effects of an educational program based on Precede-Proceed model on promoting Low Back Pain (LBP) behaviors among health care workers (HCWs). This Double-blinded randomized trial study was conducted on 112 from 120 HCWs aged from 30 to 55 years The eligible HCWs were randomly divided to intervention group 1 (N = 38), respectively intervention group 2 and control group (N = 37) for which the Precede-Proceed - based educational program was implemented and control group (N = 37). The random multi-stage cluster sampling method was used to recruit HCWs. HCWs completed a self-reported questionnaire on their Low Back Pain Behaviors assessment questionnaire based on the Precede-Proceed Model and a visual analogue scale (VAS) was also used. The data were gathered at initial of the study, 6 and 12 months follow-ups from three groups and were analyzed through SPSS version 19. There was a significant interaction between the factors "group" and "test time" (p < 0.05, p < 0.001) of knowledge, perceived self-efficacy, and attitude, reinforcing factors, enabling factors, public health, quality of life and LBP preventive behaviors of the intervention group., although, no significant alternate became located in the mean score of above structures of the control group. The findings of the present study confirmed the effectiveness of the PRECEDE-PROCEED model-based educational program on preventing LBP by enhancing scores of model constructs. However, these results should be repeated in further studies to be able to apply this program in health system. Abstract : Occupational health; Health profession; Rehabilitation; Physical activity; Public health; Quality of Lifel PRECEDE-PROCEED model; LBP, Preventive behavior, Attitude, Enabling factors, Reinforcing factors.